2007
DOI: 10.1002/jms.1185
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS ion maps for the characterization of aniline derivatives of fatty acids and triglycerides in laboratory‐denatured rapeseed oil

Abstract: In 1981 Spain went through a unique epidemic associated with a food-borne vector, affecting more than 20 000 people with over 800 deaths, which came to be known as the Toxic Oil Syndrome (TOS). Early epidemiological studies showed a link between this illness and the ingestion of rapeseed oil denatured with 2% aniline. This oil, originally aniline-denatured for industrial use, was fraudulently processed in an attempt to remove free aniline, and marketed as edible oil. Fatty acid anilides (FAA), monoesters and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These ion maps can be obtained by a longer direct infusion process with autosamplers or better by nanoESI using Nanomate (Advion Inc.) robotic injections to allow long-enough scan times. The method should not be confused with spatial ion maps obtained from secondary ion mass spectrometry TOF-SIMS [200] or mass spectrometric imaging or ion maps that refer to retention time– m/z visualizations (LC-MS ion maps) [201]. The total ion map is a function of precursor m/z value versus product ion m/z value and intensity, and it can be represented in two- or three-dimensional space.…”
Section: Mass Spectral Data Handlingmentioning
confidence: 99%
“…These ion maps can be obtained by a longer direct infusion process with autosamplers or better by nanoESI using Nanomate (Advion Inc.) robotic injections to allow long-enough scan times. The method should not be confused with spatial ion maps obtained from secondary ion mass spectrometry TOF-SIMS [200] or mass spectrometric imaging or ion maps that refer to retention time– m/z visualizations (LC-MS ion maps) [201]. The total ion map is a function of precursor m/z value versus product ion m/z value and intensity, and it can be represented in two- or three-dimensional space.…”
Section: Mass Spectral Data Handlingmentioning
confidence: 99%
“…43 Toxic oil syndrome is a unique combination of vasculitis, thrombosis, and immunologic changes (e.g., T -lymphocyte activation, cytokine release) that differs from the toxicity previously associated with refi nery products, additives, or contaminants. In a study of toxic oil syndrome -associated oils, fractionation of the oils by high performance liquid with ultraviolet detection (HPLC/UV) and analysis by high performance liquid chromatography/atmospheric pressure chemical ionization/ tandem mass spectrometry (HPLC/ APCI/MS/MS) demonstrated 115 aniline derivatives from nine aniline -related families of chemicals.…”
Section: Exposure Sourcementioning
confidence: 99%
“…A genotoxic activity of aniline and its metabolites and their relationship to the carcinogenicity of aniline in the spleen of rats was reported 10 by Ernst and Bernd. Potent genotoxicity of aminophenylnorharman, formed from aniline in the liver of gpt delta transgenic mouse was reported 11 by Ken-ichi Masumura et al Carcinogenicity of aminophenylnorharman, formed from aniline in F344 rats had been reported 12 by Toshihiko Kawamori et al A few analytical methods has also been reported for quantification of aniline such as spectrometric 13 , azo-dye formation 14 , fluorescence 15,16 , alternating-current oscillopolarographic titration 17 , NIR spectroscopy 18 , GC 19 , HPLC 20,21 and LCMS 22,23 .…”
Section: Introductionmentioning
confidence: 99%